Rekonstruksi Folklor Batak Toba dalam Bentuk Pertunjukan Tortor Sigale-Gale - Rini H. Sinaga (Gesture: Jurnal Seni Tari, 2016)
This study aims to determine how the existence of folklore in BatakToba society and pinpoint how "Reconstruction Folklore Batak Tobain the form Tortor performances Sigale-gale". For a discussion of theresearch objectives above, use the theories related to the researchtopic, such as the reconstruction theory, the theory of folklore, thetheory of forms of performance, tortor understanding, andunderstanding existence. The research was conducted to discuss"Reconstruction Folklore Batak Toba In The Form Of PerformingTortor Sigale-gale" was conducted for 2 Months namely frontier inDecember 2015 to February 2016. The research is in the area ofPangururan Samosir and Medan Helvetia. The population in thisstudy are some of the figures of young and old artists. The resultsusing qualitative research methods include the presentation andinterpretation of the data that is how "Reconstruction Folklore BatakToba In The Form Of Performing Tortor Sigale-gale. Folklore(folklore) in the Toba Batak society is a kind of oral folklore andfolklore instead of orally. Sigale-gale statue can move with thevarious movements that detail, such as hand movements up and down,rigid (staccato) and head could only shake his head. ReconstructionFolklore Sigale-gale lifted many of the artists into a work of artperformances.Performances Tortor Sigale-gale one of the creativityof young people and parents are engaged in the arts.In the form ofdance performances include the presence of motion, accompaniment,makeup, and clothing